2018
DOI: 10.1029/2017wr021857
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and Impact Assessment of Input and Parameter Uncertainty in Predicting Groundwater Flow With a Fully Distributed Model

Abstract: We present a general and flexible Bayesian approach using uncertainty multipliers to simultaneously analyze the input and parameter uncertainty of a groundwater flow model with consideration of the heteroscedasticity of the groundwater level error. Groundwater recharge and groundwater abstraction multipliers are introduced to quantify the uncertainty of the spatially distributed input data of the groundwater model in addition to parameter uncertainty. The heteroscedasticity of the groundwater level error is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 73 publications
(143 reference statements)
2
20
0
Order By: Relevance
“…As the total discharge from the model area and the mixing ratio at several cells from the two inflow sources were known, detailed data of precipitation or catchment properties were not needed for the model setup. Mustafa et al (2018) demonstrated that the input uncertainty in the catchment properties affects the model predictions and parameter distributions, and this is the dominant source of uncertainty in the groundwater flow prediction. To limit the uncertainties, the model was based on more accurate spring Fig.…”
Section: Flow Conditions and Scaling To Mar Sitesmentioning
confidence: 99%
“…As the total discharge from the model area and the mixing ratio at several cells from the two inflow sources were known, detailed data of precipitation or catchment properties were not needed for the model setup. Mustafa et al (2018) demonstrated that the input uncertainty in the catchment properties affects the model predictions and parameter distributions, and this is the dominant source of uncertainty in the groundwater flow prediction. To limit the uncertainties, the model was based on more accurate spring Fig.…”
Section: Flow Conditions and Scaling To Mar Sitesmentioning
confidence: 99%
“…The conventional treatment of uncertainty in groundwater modeling primarily focuses on parameter uncertainty, whereas uncertainties due to the model structure are often neglected (Gaganis & Smith, 2006;Rojas et al, 2008). However, many researchers have recently acknowledged that the uncertainty arising from the conceptual model structure has a significant effect on the model predictions and that parameter uncertainty does not cover the whole range of uncertainty (Bredehoeft, 2005;Højberg & Refsgaard, 2005;Mustafa et al, 2018Mustafa et al, , 2019Neuman, 2003;Poeter & Anderson, 2005;Refsgaard et al, 2006Refsgaard et al, , 2007Rojas et al, 2008;Troldborg et al, 2007). Therefore, neglecting conceptual model structure uncertainty may result in unreliable predictions and underestimation of the total predictive uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Hendricks Franssen et al (2011) reported that the EnKF significantly outperformed with synthetic experimental data compare the real data. Mustafa et al (2018) presented a Bayesian approach to simultaneously quantify parameter and input uncertainty of a groundwater flow model. The performance of this approach has been evaluated using a single conceptual real-world groundwater flow model.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations